Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fimmu.2023.1123158
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adaptive response in COVID-19 vaccine recipients and the effect of a booster dose

Abstract: We examined the immune response in subjects previously infected with SARS-CoV2 and infection-naïve 9 months after primary 2-dose COVID-19 mRNA vaccination and 3 months after the booster dose in a longitudinal cohort of healthcare workers. Nine months after primary vaccination, previously infected subjects exhibited higher residual antibody levels, with significant neutralizing activity against distinct variants compared to infection-naïve subjects. The higher humoral response was associated with higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…These results significantly correlated with specific antibodies for both isotypes. The association between antibodies, neutralizing capacity and specific circulating memory B cells have been previously described by other researchers after infection and vaccination with mRNA vaccines [22,23]. Also, it has been reported that the switch of the memory B cell compartment remains elevated after vaccination with SARS-CoV-2 mRNA vaccines [24,25].…”
Section: Discussionsupporting
confidence: 55%
“…These results significantly correlated with specific antibodies for both isotypes. The association between antibodies, neutralizing capacity and specific circulating memory B cells have been previously described by other researchers after infection and vaccination with mRNA vaccines [22,23]. Also, it has been reported that the switch of the memory B cell compartment remains elevated after vaccination with SARS-CoV-2 mRNA vaccines [24,25].…”
Section: Discussionsupporting
confidence: 55%
“…These results significantly correlated with specific antibodies of both isotypes. The association among antibodies, neutralizing capacity, and specific circulating memory B cells have been previously described after infection and vaccination with mRNA vaccines in children [24] and adults [28,29]. Also, it has been reported that the compartment of the memory B cell remains elevated after vaccination with SARS-CoV-2 mRNA vaccines [30,31].…”
Section: Discussionmentioning
confidence: 81%
“…This data is limited in the ability to detect a small effect of previous exposure by our small sample size of individuals with previous exposure. Others have shown longer-lasting immunity as exhibited by higher antibody levels and neutralization activity in those with previous infection 9 months after primary 2-dose COVID-19 mRNA vaccination ( 19 ). In the context of the high rate of breakthrough infections prior to 6 months observed in recent surges of SARS-CoV-2 infections, these data indicate that waning of antibody levels over time is not the primary driver of SARS-CoV-2 breakthrough infections.…”
Section: Discussionmentioning
confidence: 99%